Topology of the lateral visual system: The fundus of the superior temporal sulcus and parietal area H connect nonvisual cerebrum to the lateral occipital lobe - Nicholas B. Dadario; Onur Tanglay; Jordan F. Stafford; Ethan J. Davis; Isabella M. Young; R. Dineth Fonseka; Robert G. Briggs; Jacky T. Yeung; Charles Teo; Michael E. Sughrue (Brain and Behavior, 2023)
Abstract Background and Purpose Mapping the topology of the visual system is critical for understanding how complex cognitive processes like reading can occur. We aim to describe the connectivity of the visual system to understand how the cerebrum accesses visual information in the lateral occipital lobe. Methods Using meta‐analytic software focused on task‐based functional MRI studies, an activation likelihood estimation (ALE) of the visual network was created. Regions of interest corresponding to the cortical parcellation scheme previously published under the Human Connectome Project were co‐registered onto the ALE to identify the hub‐like regions of the visual network. Diffusion Spectrum Imaging‐based fiber tractography was performed to determine the structural connectivity of these regions with extraoccipital cortices. Results The fundus of the superior temporal sulcus (FST) and parietal area H (PH) were identified as hub‐like regions for the visual network. FST and PH demonstrated several areas of coactivation beyond the occipital lobe and visual network. Furthermore, these parcellations were highly interconnected with other cortical regions throughout extraoccipital cortices related to their nonvisual functional roles. A cortical model demonstrating connections to these hub‐like areas was created. Conclusions FST and PH are two hub‐like areas that demonstrate extensive functional coactivation and structural connections to nonvisual cerebrum. Their structural interconnectedness with language cortices along with the abnormal activation of areas commonly located in the temporo‐occipital region in dyslexic individuals suggests possible important roles of FST and PH in the integration of information related to language and reading. Future studies should refine our model by examining the functional roles of these hub areas and their clinical significance.